2016
DOI: 10.21511/imfi.13(3-2).2016.07
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of United States on Dow Jones Sustainability Index

Abstract: This paper examines the effect of various economic and financial indicators on the Dow Jones Sustainability Index (DJSI) returns. In particular, four explanatory variables are employed, namely United States (US) 10 Year bond value, gold price, Trade Weighted U.S. Dollar Index and Consumer Sentiment Index calculated by Michigan University. A generalized autoregressive conditional heteroskedasticity (GARCH) model is applied over DJSI United States which incorporates socially responsible companies for the period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The variation of sentiment is significant in both models, which means that the variation of sentiment influences the volatility of both indices. These results are in line with previous studies [6,7] and confirm H2. Furthermore, the coefficient is higher in the S&P 500 Environmental & Socially Responsible estimation, confirming H3.…”
Section: Garch Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The variation of sentiment is significant in both models, which means that the variation of sentiment influences the volatility of both indices. These results are in line with previous studies [6,7] and confirm H2. Furthermore, the coefficient is higher in the S&P 500 Environmental & Socially Responsible estimation, confirming H3.…”
Section: Garch Resultssupporting
confidence: 94%
“…Investor sentiment can be measured using consumer surveys [6,7], market variables [23,24], or sentiment from microblogs like Twitter [25], StockTwits [20], or Yahoo! Finance [26].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found different degrees and characteristics of correlations between the analyzed indices' performance, contributing to the optimization of sustainable investment portfolios. Giannarakis, Partalidou, Zafeiriou, and Sariannidis (), De Oliveira, Cunha, Cyrino Oliveira, and Samanez () and Mensi, Hammoudeh, Al‐Jarrah, Sensoy, and Kang () assessed the relationship between the performance of sustainability indices in both developed and developing regions and countries and the performance of other non‐stock indicators such as crude oil prices, US T‐bills, gold, the dollar and consumer sentiment. The authors found a relevant influence of these indicators on the performance of the assessed sustainability indices, which should be considered by sustainable investors.…”
Section: Sustainable Investmentmentioning
confidence: 99%
“…The specific role of gold in diversification of portfolio investment was analysed by (Sherman, 1982;Adrangi et al, 2000;Smith, 2002;Liu, & Chou, 2003;Davidson et al, 2003;Lucey, Tulley, 2006 a,b;Ibrahim, 2012;Makiel, 2015;Brycki, 2015;Bundrik, 2016;Yu, H.-C., Lee, C.-J. & Shih, T.-L., 2016;Giannarakis, G., Partalidou, X, Zafeiriou, & Sariannidis, N., 2016) and others. Nevertheless, different scientific studies often provide contradictory results concerning gold investment incentives and an optimal share of gold in an investment portfolio.…”
Section: Introductionmentioning
confidence: 99%